2019
DOI: 10.1177/1687814018819890
|View full text |Cite
|
Sign up to set email alerts
|

Grout diffusion model in porous media considering the variation in viscosity with time

Abstract: Grouting engineering is widely used in water plugging for geotechnical engineering. However, grout is usually treated as a Newton fluid and the viscosity is considered unchangeable over time during the grouting design process. This study proposes a grout diffusion model for porous media that considers the variation in viscosity with time. The flow equation is derived for a single smooth tubule. Then, the microequation of Bingham grout flowing in porous media is obtained. Finally, an assembled diffusion model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Moreover, Chinese scholars have also researched the influence of the time-varying characteristics of the cement grout on the diffusion law. Yang (2005a, b) and Hou (2019) considered the time-varying cement grout and revealed the diffusion law of time-varying Bingham fluid in porous media. However, due to the computer simulation level at that time, the simulation results of the above scholars only stayed at the level of a 1D or two-dimensional (2D) generalized model, which could not be closely combined with the actual project.…”
Section: The Research Status On Numerical Simulation Of Rock Groutingmentioning
confidence: 99%
“…Moreover, Chinese scholars have also researched the influence of the time-varying characteristics of the cement grout on the diffusion law. Yang (2005a, b) and Hou (2019) considered the time-varying cement grout and revealed the diffusion law of time-varying Bingham fluid in porous media. However, due to the computer simulation level at that time, the simulation results of the above scholars only stayed at the level of a 1D or two-dimensional (2D) generalized model, which could not be closely combined with the actual project.…”
Section: The Research Status On Numerical Simulation Of Rock Groutingmentioning
confidence: 99%
“…Some previous findings suggested that grout permeates in the laminar flow state when it is injected into the ground. Regarding the spherical diffusion model, the pores of soil layers can be considered as radial capillary tubes from center of sphere outward [35,40,41]. e size of capillary channels in the sandy layer varies significantly, and it is extremely difficult to reveal the real state through a mathematical model.…”
Section: General and Basicmentioning
confidence: 99%
“…e viscosity of cement-based grout is featured by the time-varying property. During cement hydration, the viscosity and viscous resistance of grout increase over time, causing an adverse impact on grout diffusion [41]. When grout is injected into the soil, part of cement particles is blocked by skeleton of soil particles, resulting in stagnation and filtration of these cement particles as well as decrease of grout concentration and blockage of the soil pores.…”
Section: Advances In Materials Science and Engineeringmentioning
confidence: 99%
“…Predecessors have achieved plentiful and substantial outcomes of the research on grouting. To name a few, in terms of grouting theory, the classical permeation grouting theory, compaction grouting theory, fracture grouting theory, and their optimization are proposed [7][8][9][10][11][12][13][14]; in terms of grouting material, such as cement-based slurry, sodium silicate, silica sol, and other optimized slurry materials were studied [15][16][17][18][19][20]; in terms of diffusion mechanism of grouting slurry, the slurry diffusion mechanism has been studied considering the time-varying characteristics of viscosity [21][22][23], temperature-varying characteristics [24,25], and multi-field coupling [26,27]. In the research on permeation grouting with broken surrounding rock, Pan D.J.…”
Section: Introductionmentioning
confidence: 99%